Meta-F*: Proof Automation with SMT, Tactics, and Metaprograms - Martinez, Guido; Ahman, Danel; Dumitrescu, Victor; Giannarakis, Nick; Hawblitzel, Chris; Hritcu, Catalin; Narasimhamurthy, Monal; Paraskevopoulou, Zoe; Pit–Claudel, Clément; Protzenko, Jonathan; Ramananandro, Tahina; Rastogi, Aseem; et al. (European Symposium On Programming, 2019)
We introduce Meta-F*, a tactics and metaprogramming framework for the F* program verifier. The main novelty of Meta-F* is allowing to use tactics and metaprogramming to discharge assertions not solvable by SMT, or to just simplify them into well-behaved SMT fragments. Plus, Meta-F* can be used to generate verified code automatically. Meta-F* is implemented as an F* effect, which, given the powerful effect system of F*, heavily increases code reuse and even enables the lightweight verification of metaprograms. Metaprograms can be either interpreted, or compiled to efficient native code that can be dynamically loaded into the F* type-checker and can interoperate with interpreted code. Evaluation on realistic case studies shows that Meta-F* provides substantial gains in proof development, efficiency, and robustness. Accepted for publication, to appear